Impact of Green Transformational Leadership on Employee Green Behavior : A PLS-SEM Approach - Deshpande, Pallavi; Srivastava, Anugaminipriya; Kulkarni, Medha; Lenka, Reena (Mahapatra) (Prabandhan: Indian Journal of Management, 2024)
Purpose : The purpose of this paper was to understand the impact of green transformational leadership (GTL) on employee green behavior (EGB) in the information technology (IT) sector. Methodology : For this research, the data were collected from IT employees of Pune, Maharashtra. The association between the latent variables, along with various characteristics, was observed. One hundred thirty employees from IT organizations were assessed through the survey method, and analysis was done using SPSS and the PLS-SEM approach. Findings : The empirical study showed a positive relationship between GTL and EGB. The results of the study also showcased that a green organizational identity (GOI) strongly mediated the relationship between GTL and EGB, and green training (GT) as a moderator strengthened the relationship. Practical Implications : Pro-environmental initiatives and policies cultivated an atmosphere of unity and collaboration in the workplace toward the environment. Originality/Value : This study added value to GTL. The findings would be helpful for policymakers.